1998
DOI: 10.1128/mcb.18.10.5868
|View full text |Cite
|
Sign up to set email alerts
|

The Deafness-Associated Mitochondrial DNA Mutation at Position 7445, Which Affects tRNASer(UCN) Precursor Processing, Has Long-Range Effects on NADH Dehydrogenase Subunit ND6 Gene Expression

Abstract: The pathogenetic mechanism of the deafness-associated mitochondrial DNA (mtDNA) T7445C mutation has been investigated in several lymphoblastoid cell lines from members of a New Zealand pedigree exhibiting the mutation in homoplasmic form and from control individuals. We show here that the mutation flanks the 3 end of the tRNA Ser(UCN) gene sequence and affects the rate but not the sites of processing of the tRNA precursor. This causes an average reduction of ϳ70% in the tRNA Ser(UCN) level and a decrease of ϳ4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
185
8
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 184 publications
(206 citation statements)
references
References 44 publications
(87 reference statements)
9
185
8
2
Order By: Relevance
“…In particular, mtDNA mutations at positions 4216 and 13708 labeled as second LHON mutations were implicated to increase the penetrance of the deafness-associated A7445G mutation [Guan et al, 1998], while the ND1 T3308C and tRNA Ala T5655C mutations likely contribute to the higher penetrance of deafness in an African pedigree than Japanese and French families carrying the T7511C mutation [Li et al, 2004c]. Apart from the A1555G and G7444A mutations, 36 variants in this mitochondrial genome, belonging to the Eastern Asian haplogroup D4a [Yao et al, 2002], showed no evolutionary conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, mtDNA mutations at positions 4216 and 13708 labeled as second LHON mutations were implicated to increase the penetrance of the deafness-associated A7445G mutation [Guan et al, 1998], while the ND1 T3308C and tRNA Ala T5655C mutations likely contribute to the higher penetrance of deafness in an African pedigree than Japanese and French families carrying the T7511C mutation [Li et al, 2004c]. Apart from the A1555G and G7444A mutations, 36 variants in this mitochondrial genome, belonging to the Eastern Asian haplogroup D4a [Yao et al, 2002], showed no evolutionary conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the G7444A mutation is adjacent to the site of 3' end endonucleolytic processing of the L-strand RNA precursor, spanning tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Levinger et al, 2004]. Our previous data showed that the A7445G mutation in the precursor of tRNA Ser(UCN) led to a failure in the processing of the L-strand RNA precursor, thereby causing a marked decrease of the steady-state levels of tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Li et al, 2005b]. Thus, the G7444A mutation, similar to the A7445G mutation, may also cause a defect in the processing of the L-strand RNA precursor, thus causing mitochondrial dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of pathogenic mtDNA mutations are located in genes controlling tRNA expression 41. Such mutations lead to reduced tRNA steady‐state levels, decreased mitochondrial protein synthesis, and destabilized tRNA secondary or tertiary structure42, 43 and impaired oxidative phosphorylation and oxygen consumption 43. Elsewhere, tRNA‐thr m.15294T>C and other tRNA‐thr variants have been associated with dilated cardiomyopathy 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations often occur in homoplasmy or in high levels of heteroplasmy, indicating a high threshold for pathogenicity. It is believed that mutations in this gene can cause a failure in tRNA metabolism, thereby npg leading to a decrease in the amount of affected tRNAs, which subsequently results in insufficient mitochondrial protein synthesis and the respiration defects [85].…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 99%
“…The A7445G mutation is a silent change of both the last nucleotide of the COI gene on the heavy strand and the nucleotide immediately adjacent to the 3′ end of the tRNA Ser(UCN) gene on the light strand. It is possible that the mutation may affect normal processing of the light-strand polycistronic RNA and lead to significant decreases in the levels of both tRNA Ser(UCN) and cotranscripted ND6 mRNA, which subsequently disturbs both mitochondrial protein synthesis and respiration of the mutant cells [85]. A recent study has indicated that the biochemical phenotype associated with the A7445G mutation was modified by nuclear background [87].…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 99%